OS SIGNIFICADOS DE BELEZA CORPORAL: A INFLUÊNCIA DO CONSUMO NA CONSTRUÇÃO DO CONCEITO POR MULHERES FREQÜENTADORAS DE ACADEMIAS EM CURITIBA PONTA GROSSA 2007 - Leal, Regina Bonka (2007)
This dissertation has for objective to verify which or which are the concepts of corporal beauty, for apprentices of the modality of Bodypump of the gyms of Curitiba. The Chapter I intends to present the logic of the construction of the work. The second chapter possesses as main theoretical unit to Jean Baudrillard works. A vision on the contemporary society, the mass society that is privileged and in this the subjects related to the feminine body. In this chapter he comes the Theory of Consumption proposed by Baudrillard and the lines that characterize that same society. The third chapter looks for to bring the problem inside of a linked to the broadcastings. The Chapter IV presents the understanding that is had regarding the models of bodies: body, aesthetics, corporal beauty and corporal practices of academy In the Chapter V the construction of the analysis model will be observed used. For this, the reflections of Maffesoli and his/her Theoretical "Model of Aesthetics" are used based on a composition of linked aesthetic style to the daily. In the Chapter VI they are the analyses of the data and the obtained results. It was verified that for the researched group the practice of the modality Bodypump has as main function to look for a spread beauty model for the communication means and pursued by the visitors of corporal practices of academy. After these analyses the following conclusion was arrived: the interviewees' answers show that the beauty concept is linked the corporal aesthetics in an attempt of search of the happiness.